CONCEPTUAL ANTONYMY IN PHILOSOPHICAL TERMS THE ENGLISH LANGUAGE (Proceedings of International Educators Conference, 2024)
The study of antonymy, or the relationship between opposites, is a crucial aspect of understanding linguistic and cognitive structures. In philosophical discourse, the use of antonymic pairs of terms is particularly significant, as it allows for the articulation of complex and often abstract ideas through contrast. This thesis explores the role of conceptual antonymy in the formation and communication of philosophical terms in the English language. By applying Lyons’ theory of antonymy, the research classifies and analyzes these terms to uncover the underlying principles that govern their use and their contribution to philosophical thought.